Seminiferous Cord Formation and Germ-Cell Programming: Epigenetic Transgenerational Actions of Endocrine Disruptors - SKINNER, MICHAEL K. (Ann N Y Acad Sci, 2005)
The molecular and cellular control of embryonic testis development was investigated through an analysis of the embryonic testis transcriptome to identify potential regulatory factors for male sex determination and testis morphogenesis. One critical factor identified is neurotropin 3 (NT3). At the onset of male sex determination, Sertoli cells initiate differentiation and express NT3 to act as a chemotactic factor for mesonephros cells to migrate and associate with Sertoli-germ cell aggregates to promote cord formation. Promoter analysis suggests that NT3 may be an initial downstream gene to SRY and helps promote testis morphogenesis. Endocrine disruptors were used to potentially interfere with embryonic testis development and further investigate this biological process. The estrogenic pesticide methoxychlor and antiandrogenic fungicide vinclozolin were used. Previous studies have shown that methoxychlor and vinclozolin both interfere with embryonic testis cord formation and cause increased spermatogenic cell apoptosis in the adult testis. Interestingly, transient in vivo exposure to endocrine disruptors at the time of male sex determination caused a transgenerational phenotype (F1–F4) of spermatogenic cell apoptosis and subfertility. This apparent epigenetic mechanism involves altered DNA methylation and permanent re-programming of the male germ-line. A series of genes with altered DNA methylation and imprinting are being identified. Observations reviewed demonstrate that a transient embryonic in utero exposure to an endocrine disruptor influences the embryonic testis transcriptome and through epigenetic effects (e.g., DNA methylation) results in abnormal germ-cell differentiation that subsequently influences adult spermatogenic capacity and male fertility, and that this phenotype is transgenerational through the germ-line. The novel observations of transgenerational epigenetic endocrine disruptor actions on male reproduction critically impact the potential hazards of these compounds as environmental toxins. The literature reviewed provides insight into the molecular and cellular control of embryonic testis development, male sex determination, and the programming of the male germ-line.